Bacteraemia and antibiotic susceptibility pattern of isolates from patients visiting a private hospital of Kathmandu (Tribhuvan University Journal of Microbiology, 2018)
Background: Bacteraemia can develop a broad array of complications that may be difficult to recognize initially and can increase morbidity. The study was thus conducted to identify the causative agents of bacteraemia and to assess antibiogram of the isolates among the patients suspected of blood stream infection visiting Everest hospital, New Baneshwor Kathmandu.Methods: Altogether 400 blood cultures were processed during March, 2015 to August, 2015. Standard Operating Procedures (SOPs) was followed during the processing of the specimens. Antibiotic susceptibility testing of bacterial isolates was done by Kirby Bauer disc diffusion method with Muller-Hinton agar using the guidelines and interpretive criteria of the Clinical and Laboratory Standards Institute (CLSI 2013).Result: The positivity of blood culture was found to be 48 (12%). Gram negative bacterial were found to be more predominant 27(56.2%) than gram positive bacteria 21(43.7%) in causing bacteraemia. The most prevalent isolate was Staphylococcus aureus 15 (31.2%) followed by Salmonella Paratyphi A 10 (20.8%) and Salmonella Typhi 8 (16.6%), E. coli & CoNS 4 (8.3%), Pseudomonas aeruginosa 3 (6.2%) and Klebsiella pneumoniae & Streptococcus pneumoniae 2 (4.1%) respectively. All gram-positive isolates were found to be sensitive to Cefoxitin, Ceftriaxone and Vancomycin followed by Ampicillin (90.42%), Erythromycin (85.71%), Ciprofloxacin (83.33%), Doxycycline (75%) and Cephalexin (70.58%) whereas gram negative isolates were sensitive to Ceftriaxone followed by Chloramphenicol (92%), Gentamicin (88.8%), Cefixime (85.71%), Ofloxacin (83.3%) and Amoxycillin and Ciprofloxacin (71.3%)Conclusion: The isolation of etiological agents of blood stream infection should be assessed by proper microbiological analysis and it would be helpful for controlling of the outbreaks of resistance strains through effective empirical therapy.